2018
DOI: 10.1186/s12974-018-1309-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of microglia in processing and spreading of bioactive tau seeds in Alzheimer’s disease

Abstract: BackgroundMisfolding of microtubule-associated protein tau (MAPT) within neurons into neurofibrillary tangles is an important pathological feature of Alzheimer’s disease (AD). Tau pathology correlates with cognitive decline in AD and follows a stereotypical anatomical course; several recent studies indicate that tau pathology spreads inter-neuronally via misfolded tau “seeds.” Previous research has focused on neurons as the source of these tau seeds. However, recent studies as well as the data contained herein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
189
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(205 citation statements)
references
References 56 publications
13
189
1
2
Order By: Relevance
“…Activated microglia engulf patho-proteins containing neurons flagging phosphatidylserine signals [76] and degrade via lysosomal machinery [58]. But, the failure of proper proteolysis can lead to the excretion of cleaved peptides, which acts as seed entities for further aggregation within healthy neurons [77]. In our study, we found the phagocytosis of extracellular Tau oligomers and adherence of high molecular weight Tau aggregates onto N9 microglial cells, indicating the initiation of active internalization and clearance.…”
Section: Discussionmentioning
confidence: 47%
“…Activated microglia engulf patho-proteins containing neurons flagging phosphatidylserine signals [76] and degrade via lysosomal machinery [58]. But, the failure of proper proteolysis can lead to the excretion of cleaved peptides, which acts as seed entities for further aggregation within healthy neurons [77]. In our study, we found the phagocytosis of extracellular Tau oligomers and adherence of high molecular weight Tau aggregates onto N9 microglial cells, indicating the initiation of active internalization and clearance.…”
Section: Discussionmentioning
confidence: 47%
“…As microglia do not normally express tau, this indicates that microglia had engulfed tau aggregates from the extracellular space, or as a part of engulfed debris from dead neurons. It has been shown that microglia have the ability to internalize tau to degrade it [219][220][221]. However, when the amount of aggregating protein surpasses the degradation capabilities of microglia, toxic tau aggregates appear in the cytoplasm and promote microglial dysfunction [222].…”
Section: Further Considerations For Understanding Propagation Of Tau mentioning
confidence: 99%
“…After tau seeds enter the neuron, they can leak via damaged vesicles into the cytosol and seed physiological monomers to propagate the pathological process (59,60). Additionally, microglia and astrocytes can phagocytose (61)(62)(63). The process of tau spreading is now hypothesized to underlie the progression of tau pathology throughout the brain (Figure 3).…”
Section: Tau Pathobiologymentioning
confidence: 99%